2005
DOI: 10.1111/j.1745-7254.2005.00536.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a single dose of mifepristone on expression of pinopodes in endometrial surface of mice1

Abstract: Aim: To investigate the effect of mifepristone (RU486) as a single dose on pinopodes expression in the endometrial surface of mice at the time of implantation. Methods: Pregnant mice in the treated four groups received mifepristone subcutaneously (0.1 mg) between 07:00 and 08:00 AM on Pd (day of pregnancy)1, Pd2, Pd3, and Pd4. Pregnant mice in the non‐treated group were used as controls. The uterine horns were collected randomly from two mice in each group between 21:30 and 22:00 PM on Pd4, and from another … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…But the ovaries were not affected, and the estradiol/progesterone concentrations in serum were not significantly changed. Huang et al [17] found that subcutaneous administration of a single dose of mifepristone 0.10 mg mouse À1 on Pd1, Pd2, Pd3 and Pd4 respectively inhibited the development and maturation of the endometrium, thus affecting the embryo implantation. Lai and Zhang [20] found that the levels of Dkk1 mRNA and protein in mifepristone group were significantly higher than those in the control groups, suggesting that Dkk1 probably plays an important role in signal transudation of the embryo implantation, and its expression may be up-regulated by progestogen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But the ovaries were not affected, and the estradiol/progesterone concentrations in serum were not significantly changed. Huang et al [17] found that subcutaneous administration of a single dose of mifepristone 0.10 mg mouse À1 on Pd1, Pd2, Pd3 and Pd4 respectively inhibited the development and maturation of the endometrium, thus affecting the embryo implantation. Lai and Zhang [20] found that the levels of Dkk1 mRNA and protein in mifepristone group were significantly higher than those in the control groups, suggesting that Dkk1 probably plays an important role in signal transudation of the embryo implantation, and its expression may be up-regulated by progestogen.…”
Section: Discussionmentioning
confidence: 99%
“…Mifepristone is one kind of abortion medicines and commonly used for animal abortion model. According to the reports [16][17][18], the doses of mifepristone at 3.2-4.8 mg/kg BW can markedly decrease the average number of embryos in mice. In our pretest, we injected subcutaneously the different doses (3.2, 4.0 and 4.8 mg/kg BW) of mifepristone to Kuming mice on day 4 of the pregnancy, and found that the average number of embryos in mice administered with 4.0 and 4.8 mg/kg BW of mifepristone decreased (8.1 AE 2.85 embryo numbers/per mouse or 6.4 AE 1.97 embryo numbers/per mouse; p < 0.05; n = 8).…”
Section: The Determination Doses Of Mifepristone and Baicalinmentioning
confidence: 99%
“…Mifepristone is an effective drug for termination of early pregnancy. Previous reports suggested that mifepristone administration at doses of 1.25-2.50 mg/kg BW on Pd4 had no impact on the reproduction of mice (Huang et al, 2005;Lv et al, 2012;Chen et al, 2015;Yang et al, 2016). However, mifepristone administration at doses of 0.30-2.00 mg/kg BW at approximately Pd8.5 caused 60-100% of abortions in mice (Szekeres-Bartho et al, 1997;Lv et al, 2012).…”
Section: Discussionmentioning
confidence: 93%
“…A previous study in mice reported that the ducts from the nipples and buds were beginning to appear along the smaller ducts on Pd2 or Pd3; on Pd6, alveoli formation was taking place along all the ducts; from Pd7 to Pd12, the growth and budding of mammary gland proceed steadily, and the alveoli developed thickly along ducts until Pd12 (Cole, 1933). Researchers verified that administration of mifepristone at doses of 1.25-2.50 mg/kg BW on Pd4 had little effect on the litter size in mice (Huang et al, 2005;Lv et al, 2012;Chen et al, 2015), whereas when mifepristone was administrated at doses of 0.30-2.00 mg/kg and 0.401-2.50 mg/kg, respectively, on Pd8.5 and on Pd14-19, it induced more than 60% of abortions (Szekeres-Bartho et al, 1997;Lv et al, 2012). Based on the time points of mammary gland development, and the dose range of mifepristone that induce abortion in the studies described above, we administrated mifepristone on Pd4 (0.80, 1.20, 1.60, 2.00, and 2.40 mg/kg BW), Pd8 (0.20, 0.40, 0.60, 0.80, and 1.00 mg/kg BW), and Pd12 (0.10, 0.20, 0.30, 0.40, and 0.50 mg/kg BW) in a pilot study to identify the optimum mifepristone dosage for these time points.…”
Section: Experimental Groups and Treatmentsmentioning
confidence: 99%
“…Pinopode deficiency in reproductive females undergoing in vitro fertilization (IVF) and embryo transfer treatment results in multiple implantation failures. Previous studies in humans have revealed that the window of implantation, which begins upon the formation of fully developed pinopodes, opens and closes earlier in females undergoing ovarian hyperstimulation for IVF compared with females with natural cycles ( 15 17 ). In addition, a low dose of mifepristone, which is administered as a progesterone (P4) receptor antagonist, restrains the development and maturity of pinopodes ( 18 ).…”
Section: Discussionmentioning
confidence: 99%